2022
DOI: 10.1093/ibd/izac067
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Differences in Response to Tumor Necrosis Factor Inhibitor Therapies for Ulcerative Colitis: Individual Participant Data Meta-Analyses of Clinical Trials

Abstract: Background Gender-based differences are reported in inflammatory bowel diseases (IBD) pathogenesis, but their impacts on IBD outcomes are not well known. We determined gender-based differences in response to treatment with tumor necrosis factor inhibitor (TNFi) therapies in individuals with ulcerative colitis (UC). Methods We used the Yale University Open Data Access (YODA) platform to abstract individual participant data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
2
2
0
1
Order By: Relevance
“…However, our data should be interpreted with caution because few vedolizumab-treated patients were included in our study. The association between sex and remission status at 3 months observed in our study is in line with previous findings on biological therapy ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, our data should be interpreted with caution because few vedolizumab-treated patients were included in our study. The association between sex and remission status at 3 months observed in our study is in line with previous findings on biological therapy ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…A smaller retrospective cohort study, however, demonstrated no sex-based differences in response to infliximab [28]. Finally, a recent meta-analysis was performed and demonstrated findings in line with our study, in that men were less likely to achieve clinical and endoscopic remission compared to women after completion of the induction phase, with no differences in outcomes after treatment during maintenance [29]. With vedolizumab, one study of 265 patients addressing sex differences in outcome reported that female patients were more likely to terminate use of vedolizumab due to drug intolerance [30].…”
Section: Discussionsupporting
confidence: 89%
“…Secondary analyses of individual studies have not generally shown consistent impacts of gender on treatment response ( 34 , 35 ). Two studies have suggested that men receiving golimumab or vedolizumab may have lower rates of response to induction therapy, but that this effect dissipates by the end of the maintenance phase ( 36 ). The reasons for this difference in speed of response are not well characterized.…”
Section: The Impact Of Sex and Gender On Healthcare Utilizationmentioning
confidence: 99%